2019
DOI: 10.3390/su11051290
|View full text |Cite
|
Sign up to set email alerts
|

Universal Welfare May Be Costly: Evidence from School Meal Programs and Student Fitness in South Korea

Abstract: The Free School Meal Program (FSMP) initiated in 2011 in South Korea allows participating schools to provide free lunches to all students regardless of their household income. This paper examines how universal free school meal programs are associated with student health outcomes. We empirically show that FSMP reduces the share of students with high fitness grades by up to 1.5% of the student population. We also find that expenses for physical education decrease in schools that adopt FSMP. These results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…Understanding their own achievement should lead to the formation of beneficial relationships with authority figures, including teachers. A previous study found that female student-athletes with higher HP scores are likely to have better peer relationships, similar to a study on health concerns of middle school girls [34]. Notably, female students are more likely to discuss physical health concerns such as menstruation with their friends than their parents or managers [35][36][37].…”
Section: Discussionsupporting
confidence: 66%
“…Understanding their own achievement should lead to the formation of beneficial relationships with authority figures, including teachers. A previous study found that female student-athletes with higher HP scores are likely to have better peer relationships, similar to a study on health concerns of middle school girls [34]. Notably, female students are more likely to discuss physical health concerns such as menstruation with their friends than their parents or managers [35][36][37].…”
Section: Discussionsupporting
confidence: 66%
“…Also, free school lunch for all middle school students in New York city had improved weight outcomes, especially for non-poor students [42]. However, one South Korean study suggested a negative relationship between free school meal programs and student tness due to the lack of physical education [43]. Public school students in LA under reduced-price school meal program or free school meal program had a higher likelihood of becoming overweight [44].…”
Section: Discussionmentioning
confidence: 99%